Tuning the morphology and energy levels in organic solar cells with metal–organic framework nanosheets - Sasitharan, Kezia; Frisch, Johannes; Kuliček, Jaroslav; Iraqi, Ahmed; Lidzey, David G.; Bär, Marcus; Rezek, Bohuslav; Foster, Jonathan A. (Scientific Reports, 2024)
Metal–organic framework nanosheets (MONs) have proved themselves to be useful additives for enhancing the performance of a variety of thin film solar cell devices. However, to date only isolated examples have been reported. In this work we take advantage of the modular structure of MONs in order to resolve the effect of their different structural and optoelectronic features on the performance of organic photovoltaic (OPV) devices. Three different MONs were synthesized using different combinations of two porphyrin-based ligands meso-tetracarboxyphenyl porphyrin (TCPP) or tetrapyridyl-porphyrin (TPyP) with either zinc and/or copper ions and the effect of their addition to polythiophene-fullerene (P3HT-PC71BM) OPV devices was investigated. The power conversion efficiency (PCE) of devices was found to approximately double with the addition of MONs of Zn2(ZnTCPP) -4.7% PCE, 10.45 mA/cm2 short-circuit current density (JSC), 0.69 open-circuit voltage (VOC), 64.20% fill-factor (FF), but was unchanged with the addition of Cu2(ZnTPyP) (2.6% PCE, 3.68 mA/cm2JSC, 0.59 VOC, 46.27% FF) and halved upon the addition of Cu2(CuTCPP) (1.24% PCE, 6.72 mA/cm2JSC, 0.59 VOC, 56.24% FF) compared to devices without nanosheets (2.6% PCE, 6.61 mA/cm2JSC, 0.58 VOC, 56.64% FF). Our analysis indicates that there are three different mechanisms by which MONs can influence the photoactive layer – light absorption, energy level alignment, and morphological changes. Analysis of external quantum efficiency, UV–vis and photoelectron spectroscopy data found that MONs have similar effects on light absorption and energy level alignment. However, atomic force and Raman microscopy studies revealed that the nanosheet thickness and lateral size are crucial parameters in enabling the MONs to act as beneficial additives resulting in an improvement of the OPV device performance. We anticipate this study will aid in the design of MONs and other 2D materials for future use in other light harvesting and emitting devices.
CRIS-Team Scopus Importer:2025-02-04